Differential glucose requirement in skin homeostasis and injury identifies a therapeutic target for psoriasis. (May 2018) - Zhang, Zhuzhen; Zi, Zhenzhen; Lee, Eunice; Zhao, Jiawei; Contreras, Diana; South, Andrew; Abel, E.; Chong, Benjamin; Vandergriff, Travis; Hosler, Gregory; Scherer, Philipp; Mettlen, Marcel; et al.
Abstract Proliferating cells, compared with quiescent cells, are more dependent on glucose for their growth. Although glucose transport in keratinocytes is mediated largely by theGlut1 facilitative transporter, we found that keratinocyte-specific ablation ofGlut1 did not compromise mouse skin development and homeostasis. Ex vivo metabolic profiling revealed altered sphingolipid, hexose, amino acid, and nucleotide metabolism inGlut1 -deficient keratinocytes, thus suggesting metabolic adaptation. However, culturedGlut1- deficient keratinocytes displayed metabolic and oxidative stress and impaired proliferation. Similarly, Glut1 deficiency impaired in vivo keratinocyte proliferation and migration within wounded or UV-damaged mouse skin. Notably, both genetic and pharmacologicalGlut1 inactivation decreased hyperplasia in mouse models of psoriasis-like disease. Topical application of a Glut1 inhibitor also decreased inflammation in these models. Glut1 inhibition decreased the expression of pathology-associated genes in human psoriatic skin organoids. Thus, Glut1 is selectively required for injury- and inflammation-associated keratinocyte proliferation, and its inhibition offers a novel treatment strategy for psoriasis. Keratinocytes require glucose for injury- or inflammation-driven but not homeostatic proliferation, and glucose-transport blockade blocks psoriasis-like pathology in experimental models.